The Role of Artificial Intelligence in Optimizing Electronic Health Records for Early Detection of Disease - Yuda Syahidin; Ade Irma Suryani (Dinasti International Journal of Education Management And Social Science, 2025)
The Role of Artificial Intelligence in Optimizing Electronic Health Records for Early Detection of Disease is a critical focus area, as AI technologies enhance the ability to analyze vast datasets within EHRs, facilitating timely identification of health risks and improving patient outcomes. By leveraging AI, healthcare providers can streamline data management processes and support more accurate and efficient predictions, ultimately leading to better disease management and resource allocation. This paper emphasizes the importance of integrating artificial intelligence into EHR systems to maximize their potential for early disease detection and improve overall healthcare delivery.